Spectrum analysis at Florida Department of Citrus - Perkin-Elmer Corporation (1970)
General view of research chemist Dr. Russell Rouseff analyzing the spectrum produced by a Perkin-Elmer fluorescence spectrophotometer in use at the Florida Department of Citrus research laboratory located in Lake Alfred, Florida. Per notations accompanying the photograph, the instrument is being used in conjunction with a liquid chromatograph to investigate the constituents of citrus fruits and juices down to minute quantities.
Keywords: Citrus fruits; Liquid chromatography; Employees; Perkin-Elmer Corporation; Scientific apparatus and instruments; Chemists; Corporations; Florida Citrus Commission. Department of Citrus; Fluorescence spectroscopy